A H∞ control for optimizing the advanced oxidation processes—Case of a catalytic ozonation reactor. (November 2015) - Abouzlam, Manhal; Ouvrard, Régis; Mehdi, Driss; Pontlevoy, Florence; Gombert, Bertrand; Karpel Vel Leitner, Nathalie; Boukari, Sahidou
Abstract: In wastewater treatment, advanced oxidation processes are largely accepted as efficient technologies. Unfortunately, in general, these approaches present a high operating cost due to an open-loop implementation, i.e. the inlet reagent is introduced in excess in order to respect discharge standards. Therefore a mixture between automatic control techniques and chemical engineering expertise should significantly improve and expand their industrial applications via closed-loop implementations. More precisely, the present paper deals with a catalytic ozonation reactor where the main objective is to reduce the oxygen consumption by minimizing the ozone overproduction. For this end, a H ∞ control strategy is used in order to obtain a significant abatement of the pollutant, and by the way illustrates the gain one can expect when applying such techniques to this kind of process. Abstract : Highlights: The closed-loop control for water treatment by AOP gives significant reagent savings. We address the problem of disturbance attenuation through the H ∞ synthesis. The set-point tracking is achieved by PI controllers. A closed-loop stability analysis with respect to time delays is developed. All developments are applied to a catalytic ozonation pilot.